MUCOEPIDERMOID CARCINOMA - RARE PRESENTATION OF CHILDHOOD CHRONIC RESPIRATORY SYMPTOMS IN 10 YEARS OLD GIRL - Shah, Syed Sajid hussain; Aalia, Bibi (Journal of Ayub Medical College Abbottabad, 2020)
Mucoepidermoid carcinoma is the rarest presentation in children arising from bronchial glands with low potential for malignancy as most of children have history of recurrent chest infections. We present the case of ten years old girl presenting with history of recurrent respiratory infections in past admitted for fever, cough and respiratory distress. HRCT showed soft tissue in lumen of trachea at level of carina extending into right main bronchus along with collapse of apical segment of right upper lobe and right middle and lower lobes collapse consolidation. Surgery was done and histopathology showed low grade mucoepidermoid carcinoma with clear histopathology of regional lymph nodes. Follow up of patient done for two years. Informed consent was taken from patient prior to writing of this case report. Keywords: cough; recurrent chest infection; carcinoma, Mucoepidermoid Carcinoma